Dari Pewahyuan Progresif Menuju Tafsir Pembebasan: Telaah Atas Hermeneutika al-Qur'an Farid Esack - Iswahyudi Iswahyudi (IAIN Ponorogo, 2011)
Polytheism and unjust social power haven been conceptually rejected by the Qur’an. Unfortunattely, its religious message is not properly understood by many Moslem scholars. They interpret it to legitimate their own interests which are sometimes contradictory to the spirit of the Qur’an. This phenomenon happens in South Africa. Farid Esack, a Muslim intellectual in this region, proposes to read the Qur'an in different direction, namely to deconstruct reading which is according to him perpetuate political interest and oppression. Esack critically reconstructs tafsir-method of the Qur'an for the purpuse of liberating Moslems. To do so, he proposes the interpretation concept which is based on some principles and key words of the Qur'an. His concern of liberating Moslems is transparent in his hermeneutical endeavour. For that reason discussing Esack’s hermeneutics is still significant and relevant to the discourse on current Qur ’anic studies. Esack’s proposals are elucidated in this article.